A qualitative study of the views and experiences of those working in residential children's homes - Lucy Abraham; Sarah Elgie; Vera Soares; Caroline Beale; Rachel Hiller (Scottish Journal of Residential Child Care)
Young people in residential children's homes have typically experienced significant child maltreatment and will have likely experienced multiple placement moves; both are associated with a range of poor outcomes and impact on wellbeing. Whilst much is understood about the impact of child maltreatment, little is known about how residential health care workers experience and understand the potential difficulties the children they look after experience. Our study aimed to gain an insight into the views of residential workers, how they understand their role, and what barriers they experience in their work, as well as supportive factors. We used a qualitative design to understand residential workers' perspectives of supporting their young people. Five focus groups were run with a total of 22 participants. Participants were predominantly female and ranged in age and years of experience within the sector. Participants worked in five residential care homes across England and Wales. Three core themes were identified using thematic analysis. Firstly, residential workers feel this is a rewarding profession but not one that is well understood and valued by society. Secondly, factors such as shift demands and managing challenging behaviour can be barriers to residential workers being emotionally available to the children in their care, but factors such as being part of a cohesive team and access to reflective spaces help promote resilience. Thirdly, workers recognise that confidence and skill impact their ability to successfully manage challenging behaviours. The implications of the findings can be used within children's services to promote workers' wellbeing, to reduce staff burnout and secondary trauma, and to improve retention, which can increase positive outcomes for young people in their care and can guide practice within the residential care sector.